Gereja Memperjuangkan Keadilan dalam Kajian “Theory of Justice” John Rawls - Mite, Arkadius (Proceedings of The National Conference on Indonesian Philosophy and Theology, 2024)
This article talks about the political and ethical duties of the Church in fighting for justice and the contribution of Rawls' Thought to the Church's struggle. The issue of justice is the responsibility of all social institutions. The church as a social institution is involved in it. The presence of the Church in social society has raised questions about whether it is appropriate for the Church to be actively involved in fighting for justice. The Church's struggle in overcoming social problems is not due to social demands themselves but rather the Church's initiative to embrace them as brothers. The value that the Church strives for is justice. Justice as an integral part of the mission of the Kingdom of God. Justice is the main problem in national and state life. The priority of justice is poverty. Poverty is caused by structures that ignore human equality and human dignity. Human dignity is the Church's mission in fighting for justice through the values of the kingdom of God. These values of the Kingdom of God are actualized by the Church in its mission.AbstrakArtikel ini berbicara tentang tugas politis dan etis Gereja dalam memperjuangkan keadilan dan sumbangan Pemikiran Rawls bagi perjuangan Gereja tersebut. Persoalan keadilan merupakan tanggung jawab semua institusi sosial. Gereja sebagai institusi sosial terlibat di dalamnya. Kehadiran Gereja dalam sosial kemasyarakatan menuai tanya, pantaskah Gereja terlibat aktif dalam memperjuangkan keadilan. Perjuangan Gereja dalam mengatasi permasalahan sosial bukan karena tuntutan sosial itu sendiri melainkan inisiatif Gereja yang merangkul sebagai saudara. Nilai yang diperjuangkan Gereja adalah keadilan. Keadilan sebagai bagian integral dari misi Kerajaan Allah. Keadilan merupakan permasalahan utama dalam kehidupan berbangsa dan bernegara. Prioritas keadilan adalah kemiskinan. Kemiskinan disebabkan oleh struktur yang mengabaikan kesetaraan manusia dan martabat manusia. Martabat manusia adalah misi Gereja dalam memperjuangkan keadilan melalui nilai-nilai kerajaan Allah. Nilai-nilai Kerajaan Allah ini diaktualisasikan oleh Gereja dalam perutusannya.